Pengaruh lingkungan keluarga dan motivasi berwirausaha terhadap intensi berwirausaha siswa SMK - Manurung, Erick Willy Stevant; Syarif, Agus; Sari, Novita (Jurnal Dinamika Manajemen, 2022)
This study aims to determine the effect of family environment and entrepreneurial motivation on vocational student entrepreneurship intentions (case studies on SMK N 2 Payakumbuh). The population in this study were students of class X SMK N 2 Payakumbuh with 100 respondents. The data collection methods used were questionnaires. The analytical tool used in this study is the instrument test consisting of validity and reliability test, multiple linear regression analysis, t-test, f test, and coefficient of determination. The whole investigation was calculated using the SPSS ver 22 program. The results showed that the family environment and entrepreneurial motivation positively and significantly affected entrepreneurial intentions. Â